Synthesis of the Results of the Trial of the Pocket Book on Early Intervention for Children with Special Needs with Hearing Impairments: A Qualitative Descriptive Study - Lilis Suhaila Nur Aini; Debora Dian Talenta Simanjuntak; Indah Nirmala Habsari; Sekar Auwalia Riswana (Universitas Negeri Surabaya, 2026)
Early intervention is an essential approach in supporting the development of children with special needs who have hearing sensory impairments, particularly in the areas of communication, language, and social interaction. One effort to support the implementation of early intervention is the provision of practical guidance media that is easy to understand and use by teachers and parents. This study aims to synthesize the results of testing a pocket book on early intervention for children with special needs and hearing sensory disorders as a medium to support the implementation of early intervention in educational and family environments. This study used a qualitative descriptive method with research subjects involving parents of children with hearing sensory disorders who participated in a pocket book trial. Data collection was conducted through observation,semi-structure interviews, and documentation. Data validity was ensured through triangulation techniques, while data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the pocket book is considered to have clear content, ease of use, and relevance to the early intervention needs of children with hearing sensory disorders. Based on the results of the trial synthesis, it can be concluded that the early intervention pocket book has the potential to be an effective and relevant supporting medium for the implementation of early intervention for children with special needs who have hearing sensory impairments.